Fat extract improves fat graft survival via proangiogenic, anti-apoptotic and pro-proliferative activities - Zheng, Hongjie (Stem Cell Res Ther, 2019)
BACKGROUND: Our previous study proved that nanofat could enhance fat graft survival by promoting neovascularization. Fat extract (FE), a cell-free component derived from nanofat, also possesses proangiogenic activity. OBJECTIVES: The aim of this study was to investigate whether FE could improve fat graft survival and whether FE and nanofat could work synergistically to promote fat graft survival. The underlying mechanism was also investigated. METHODS: In the first animal study, human macrofat from lipoaspirate was co-transplanted into nude mice with FE or nanofat. The grafts were evaluated at 2, 4 and 12 weeks post-transplantation. In the second animal study, nude mice were transplanted with a mixture of macrofat and nanofat, followed by intra-graft injection of FE at days 1, 7, 14, 21 and 28 post-transplantation. The grafts were evaluated at 12 weeks post-transplantation. To detect the mechanism by which FE impacts graft survival, the proangiogenic, anti-apoptotic and pro-proliferative activities of FE were analysed in grafts in vivo and in cultured human vascular endothelial cells (HUVECs), adipose-derived stem cells (ADSCs) and fat tissue in vitro. RESULTS: In the first animal study, the weights of the fat grafts in the nanofat- and FE-treated groups were significantly higher than those of the fat grafts in the control group. In addition, higher fat integrity, more viable adipocytes, more CD31-positive blood vessels, fewer apoptotic cells and more Ki67-positive proliferating cells were observed in the nanofat- and FE-treated groups. In the second animal study, the weights of the fat grafts in the nanofat+FE group were significantly higher than those of the fat grafts in the control group. In vitro, FE showed proangiogenic effects on HUVECs, anti-apoptotic effects on fat tissue cultured under hypoxic conditions and an ability to promote ADSC proliferation and maintain their multiple differentiation capacity. CONCLUSIONS: FE could improve fat graft survival via proangiogenic, anti-apoptotic and pro-proliferative effects on ADSCs. FE plus nanofat-assisted fat grafting is a new strategy that could potentially be used in clinical applications.